Multifunctional Logic Demonstrated in a Flexible Multigate Oxide‐Based Electric‐Double‐Layer Transistor on Paper Substrate. (10th February 2017) - Shao, Feng; Feng, Ping; Wan, Changjin; Wan, Xiang; Yang, Yi; Shi, Yi; Wan, Qing
Abstract : Paper electronics represents a newly raised concept that includes various types of electronic devices and circuits on paper. In this work, the authors report multigate oxide‐based homojunction electric‐double‐layer thin‐film transistors (TFTs) with cellulose nanofibers electrolyte film as the gate dielectrics on paper substrate. These flexible TFTs exhibit high performance with a high ON/OFF ratio of 10 7 and a high mobility of around 26 cm 2 V −1 s −1 . Resistor‐loaded inverters are demonstrated both in a bottom‐gate mode and an in‐plane‐gate mode. Logic AND operation is realized in a device with two in‐plane gates. Significantly, the universal logic NAND is experimentally demonstrated using a one transistor/one resistor structure by combining NOT and AND logics together. The paper‐based TFT devices are very interesting for emerging areas such as disposable paper electronics and sensors. Abstract : Thanks to the high electric double layer capacitance of cellulose nanofiber dielectrics, flexible oxide‐based thin‐film transistors on paper substrate exhibit high performance with a high ON/OFF ratio of 10 7 and a high mobility of 26 cm 2 V −1 s −1 . Furthermore, multifunctional logic operation is demonstrated using a one transistor/one resistor structure.